Financial Performance Analysis In The Multiple Business Cooperative "Bina Business Independent" Jombang District - Yanita, Chlaudya Agus; Sucipto, Hadi (Jurnal Sains dan Teknologi, 2023)
This study aims to determine the Financial Performance of the Multi-Business Cooperative (KSU) “Independent Business Development” in Jombang Regency. The benefits of this research are as one of the references in making decisions and determining future policies, especially in the field of cooperative financial performance. The variable in this study is financial performance, with research informants being management and cooperative members. In this study, the determination of informants was carried out using a purposive technique, in which informants were selected based on certain considerations and predetermined criteria. Data collection uses documentation and observation techniques, while the data analysis technique used is Manual Data Analysis Procedures (MDAP). The results of the study show that the financial performance of KSU Bina Usaha Mandiri is in accordance with the Decree of the Minister of Cooperatives and Small and Medium Enterprises Number 10/Per/M.KUKM/V/2016. It is proven in the aspects of capital, quality of productive assets, management, efficiency, liquidity, independence and growth and identity of KSU Bina Usaha Mandiri which have been carried out well.